2019
DOI: 10.1021/acsabm.9b00381
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatically Assembled Multilayered Films of Biopolymer Enhanced Nanocapsules for on-Demand Drug Release

Abstract: We describe layer-by-layer (LbL) buildup and pH-responsive behavior of multilayer films of alginate/chitosan/ alginate -modified silica nanocapsules (SNCs) and chitosan (CS) biopolymers via electrostatic interaction. The SNC/CS films exhibit pH-triggered swelling/deswelling transitions under physiological conditions. Fulvestrant, an FDA-approved selective estrogen receptor down-regulator agent for the treatment of breast cancer, was encapsulated in SNCs and further incorporated into the LbL films. The drug rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(24 citation statements)
references
References 69 publications
0
22
0
Order By: Relevance
“…Despite this assumption, the assessment of the homogeneous coating on the spherical surface of the particles and the coating thickness cannot be clearly evaluated by using FE-SEM images. In fact, the thickness of the multi-layer system is usually evaluated by ellipsometric measurements or Atomic Force Microscopy (AFM) after the deposition on a flat substrate, which allows the homogeneous coating of the surface [43]. However, FE-SEM observations confirmed that the LbL procedure and the subsequent ibuprofen loading did not significantly affect the morphology of both the particles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this assumption, the assessment of the homogeneous coating on the spherical surface of the particles and the coating thickness cannot be clearly evaluated by using FE-SEM images. In fact, the thickness of the multi-layer system is usually evaluated by ellipsometric measurements or Atomic Force Microscopy (AFM) after the deposition on a flat substrate, which allows the homogeneous coating of the surface [43]. However, FE-SEM observations confirmed that the LbL procedure and the subsequent ibuprofen loading did not significantly affect the morphology of both the particles.…”
Section: Resultsmentioning
confidence: 99%
“…At variance, this band is clearly not detectably visible for the Cu_SG_CIC spectrum, most likely due to the low quantity of loaded ibuprofen. In the last region of the spectra (1369-1458) the peaks can be imputed to CH 2 bending of the chitosan, alginate, and ibuprofen [41,43].…”
Section: Resultsmentioning
confidence: 99%
“…The formulations might be minimized by reducing NP doses. Primarily, the addition of adjuvants with a lower price or formulating composite NPs can boost the therapeutic efficiency [154]. Second, specific or sustained drug delivery and release can be exploited, such as microneedle methods, NP layered self-assembly, and controlled release of laden medicines maintained by nanoscale systems [155][156][157].…”
Section: Lacunae In the Current Researchmentioning
confidence: 99%
“…Zhang et al investigated in detail the grooves on alginate microfibers prepared by microfluidic spinning in different concentrations of alginate in deionized water [ 167 ]. Alginate/chitosan/alginate-modified silica nanocapsules and chitosan multilayer films were investigated during pH-triggered swelling and deswelling, and topography measurements by AFM were used to verify that their structural integrity in PBS was maintained [ 168 ].…”
Section: Applicationsmentioning
confidence: 99%